Effect of using rehabilitative exercises associated with low-intensity lasers to improve muscle strength and range of motion for those with shoulder joint immobility - Khalil, Lamyaa Abdul-Sattar (International Journal of Psychosocial Rehabilitation, 2020)
The researcher used the experimental method with the two sets of equivalents pre and post tests. Each group to match the nature of the problem. The experimental approach "represents the most accurate types of scientific research that can influence the relationship between the independent variable and the dependent variable through experience"